Latest developments on Streptococcus suis: an emerging zoonotic pathogen: part 1. - Segura, M; Zheng, H; de Greeff, A; Gao, G; Grenier, D; Jiang, Y; Lu, C; Maskell, D; Oishi, K; Okura, M; Osawa, R; Schultsz, C; et al. (Future Medicine Ltd., 2014)
First International Workshop on Streptococcus suis, Beijing, China, 12-13 August 2013 The first international workshop on Streptococcus suis, which is an important swine pathogen and emerging zoonotic agent, took place in Beijing, jointly organized by the Faculty of Veterinary Medicine, University of Montreal, Canada and the National Institute for Communicable Disease Control and Prevention, China CDC. The aim of the meeting was to gather together, for the first time, more than 80 researchers working on S. suis, from countries including China, Canada, Japan, The Netherlands, Germany, Thailand, the UK and Vietnam. This article, the first of a two-part report on this First International Workshop, reviews current aspects of the epidemiology and population genomics of S. suis, covers public health concerns and discusses questions about S. suis serotyping and molecular diagnostics.